Bimbingan Kelompok Pola BMB3 untuk Peningkatan Pengendalian Diri Korban Bencana dalam Mengatasi PTSD - Jeki Van Helen; Marjohan Marjohan; Alizamar Alizamar (Universitas Kanjuruhan Malang, 2019)
This study aims to understand the empirical conditions of the self-control ability of disaster victims who have PTSD and counseling services to overcome them. An explorative quantitative method is used by involving 41 adolescent disaster victims. Self-control is measured using the self-control scale with a reliability of 0.90. The results showed that respondents had low self-control, making them vulnerable to PTSD. Group guidance with BMB3 patterns are believed to be appropriate for facilitating victims.